2018
DOI: 10.1002/cpps.62
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for Predicting Protein‐Protein Interactions Using Various Protein Features

Abstract: Understanding protein-protein interactions (PPIs) in a cell is essential for learning protein functions, pathways, and mechanism of diseases. PPIs are also important targets for developing drugs. Experimental methods, both small-scale and large-scale, have identified PPIs in several model organisms. However, results cover only a part of PPIs of organisms; moreover, there are many organisms whose PPIs have not yet been investigated. To complement experimental methods, many computational methods have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 220 publications
0
41
0
Order By: Relevance
“…POLA1 is linked to MCM4 protein expression. Gene coexpression analysis can provide insight into functional associations because interacting protein pairs tend to behave similarly across different expression conditions (19). This approach indicated that POLA1 expression is coregulated with genes encoding other subunits of the Pol-α/primase complex, along with genes in the DNA damage response and cell cycle regulation, including MCM4 (summary data presented in Table 3, entire analysis available in Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…POLA1 is linked to MCM4 protein expression. Gene coexpression analysis can provide insight into functional associations because interacting protein pairs tend to behave similarly across different expression conditions (19). This approach indicated that POLA1 expression is coregulated with genes encoding other subunits of the Pol-α/primase complex, along with genes in the DNA damage response and cell cycle regulation, including MCM4 (summary data presented in Table 3, entire analysis available in Supplemental Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…For sequence-based pair-wise PPI prediction (37), the amino acid sequences of Cyanothece 51142 proteins were downloaded from CyanoBase (http://genome.annotation.jp/CyanoBase) (38). The experimental results contained GeneBank protein IDs starting with “gi” and were converted into RefSeq ID following instructions on the GenBank webpage and the UniProt database (39).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…ML works on numerical representation of proteins; hence physical and chemical descriptors were developed to represent proteins [ 8 , 9 , 10 ] and used to predict PPI [ 11 , 12 ]. Other descriptors, such as proteins sequence composition [ 13 , 14 ], genomic data [ 15 , 16 ], and protein three-dimensional (3D) structures [ 17 , 18 ], among others [ 19 , 20 ], were described to represent proteins to predict PPI.…”
Section: Introductionmentioning
confidence: 99%